Three pillars of skepticism in classical India Nāgārjuna, Jayarāśi, and Śrī Harṣa - Mills, Ethan (Lexington Books, 2018)
This book argues that the philosophical history of India contains a tradition of skepticism about philosophy represented most clearly by three figures: Nāgārjuna, Jayarāśi, and Śrī Harṣa. Furthermore, understanding this tradition ought to be an important part of our contemporary metaphilosophical reflections on the purposes and limits of philosophy
6.5 Śrī Harṣa's Development of Upaniṣadic Mystical Skepticism
Keywords: Nāgārjuna -- ca. 2. Jh.; Śrīharṣa -- ca. 12. Jh.; Jayarāśi Bhaṭṭa -- ca. 8. Jh.; Ideengeschichte 100-1200; Indische Philosophie; Skeptizismus; Nāgārjuna / 1911-1998; Jayarāśibhaṭṭa / active 8th century; Śrīharṣa / active 12th century; Philosophy, Indic; Skepticism / India; PHILOSOPHY / Eastern